THE POLITICS OF HUNGARIAN SOVEREIGHTY - L. A. Yurasova (Vestnik MGIMO-Universiteta)
The article analyzes main aspects of V. Orban's policy of strengthening Hungarian economic sovereignty. The Hungarian leadership had to find out balanced and reasonable approach to tackle the world economic crisis. Hungarian ballot package included reform of economic regulation on a state's level, taking moderate protectionist measures and foreign trade diversification. V. Orban's government succeeded in constitutional reform that allowed to consolidate power to deliver coherent economic policy and to harmonize separation of powers with that goal to be reached. Moreover, transferring of economic regulation to constitutional level lead to stabilization of monetary sphere. V. Orban's government enhanced state sector of economy in vulnerable areas, rose taxation on large business and shrank loans' burden of citizens in order to maintain positive economic growth. This measures ensured potential to advance further inside demand rates and to galvanize market capacity. Finally, V. Orban announced "openness to the East" policy aimed at diversifying foreign trade of Hungary. The main focus of the policy was trade with China and Russia. However, supranational authorities of European Union objected this policy goals on the grounds of economic and political consideration. But Hungarian leadership advocated its policy in a very tough way, which is a good example of self-reliance and pragmatism for the future of Europe.